Bentuk dan Makna Prefiks pada Teks Biografi: Studi Kasus Karangan Biografi Siswa SMA di Indramayu: The Form and Meaning of Prefixes in Biographical Texts: A Case Study of Biographical Essays by High School Students in Indramayu - Syehilla Syehilla; Yunus Sulistyono (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
Writing biographical texts requires students to organize a character's life story chronologically and in an informative manner, using appropriate linguistic rules. One important linguistic aspect of writing is morphology, especially the affixation process through prefixes. However, in practice, inaccuracies in the use of prefixes persist, necessitating analysis of students' morphological abilities. This study aims to identify the form and describe the meaning of prefixes in biographical texts written by high school students in Indramayu Regency. This study uses a qualitative descriptive method. The research data consist of sentences containing prefixes from students' biographical texts. The data sources come from 62 students in grades X-9 and X-10. Data collection techniques involve observation and documentation, while data analysis includes data collection, data reduction, data presentation, and conclusion. The study found six types of prefixes: me-, ber-, di-, ter-, pe-, and se-. The prefix me- is the most dominant, with 79 data points (43.89%), followed by ber- with 46 data points (25.56%). The prefixes di- and pe- each had 17 data points (9.44%), the prefix ter- had 13 data points (7.22%), and the prefix se- was the least used, with 8 data points (4.44%). In terms of form, the prefixes me-ber-, and pe- experienced allomorphic variations due to morphophonemic processes, while di-, ter-, and se- remained relatively constant. In terms of meaning, each prefix conveys a distinct grammatical function, such as expressing actions, conditions, actors, or levels. Students already have a basic understanding of the use of prefixes, but still need improvement to be more precise, varied, and contextual in their writing of biographical texts.